Pengaruh Layanan Distribusi dan Aluran Pemasaran Terhadap Volume Penjualan BBM Solar di SPBU 14.228.346 PT. DUTA SELATAN CEMERLANG KOTA GUNUNGSITOLI - Nurdelima Harefa; Maria Magdalena Bate'e; Yuterlin Zalukhu; Eduar Baene (Visi Sosial Humaniora, 2025)
In this research, we will thoroughly discuss the impact of information technology on public administration theory and practice, as well as its positive and negative implications in the government context. This research uses the literature study method as its main approach. Even though advances in information technology have brought a number of positive changes to public administration in Indonesia, there are still several obstacles that need to be overcome so that the benefits can be felt to the maximum. The concept of e-government refers to the use of information and communication technology by the government, which can improve interaction between government, society and other sectors. The impact of information technology on public administration theory and practice has significant implications, including increased efficiency, transparency, and accessibility of services. Information technology enables the automation of administrative processes, increases transparency by providing public access to government information, accelerates public services, supports data-based decision making, increases public participation, and facilitates collaboration between government agencies. However, the implementation of information technology faces a number of challenges, including limited resources, unequal access, regulatory uncertainty, and resistance to change. To maximize the benefits, ongoing investment and efforts are needed to overcome these challenges.